2007
DOI: 10.1186/1471-2334-7-105
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcus aureus intestinal colonization is associated with increased frequency of S. aureuson skin of hospitalized patients

Abstract: Background: Intestinal colonization by Staphylococcus aureus among hospitalized patients has been associated with increased risk of staphylococcal infection and could potentially contribute to transmission. We hypothesized that S. aureus intestinal colonization is associated with increased frequency of S. aureus on patients' skin and nearby environmental surfaces.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
69
0
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(78 citation statements)
references
References 17 publications
6
69
0
3
Order By: Relevance
“…It was also reported that patients with intestinal and nasal colonization of S. aureus had higher frequencies of incontinence or diarrhea than patients without S. aureus colonization. This may significantly contribute to the observed trend toward increased contamination of environmental surfaces [44,45]. The latter studies also substantiated that patients who have diarrheal stools and heavy gastro-intestinal colonization with MRSA are associated with significantly greater environmental MRSA contamination than patients without MRSA in their stools.…”
Section: Intestinal or Perineal Carriage As A Risk Factor For Dissemisupporting
confidence: 59%
“…It was also reported that patients with intestinal and nasal colonization of S. aureus had higher frequencies of incontinence or diarrhea than patients without S. aureus colonization. This may significantly contribute to the observed trend toward increased contamination of environmental surfaces [44,45]. The latter studies also substantiated that patients who have diarrheal stools and heavy gastro-intestinal colonization with MRSA are associated with significantly greater environmental MRSA contamination than patients without MRSA in their stools.…”
Section: Intestinal or Perineal Carriage As A Risk Factor For Dissemisupporting
confidence: 59%
“…With an aim to expand the application potential of these strains, it was envisaged that determination of the adhesion potential of the strains to the ECM would be pertinent, as adhesion to ECM molecules such as collagen and mucin is considered as a cardinal feature of probiotic strains (Lebeer et al, 2008). The ability of the pathogen S. aureus to colonize the intestine in conjunction with its ability to adhere to ECM molecules is a serious healthcare concern and has been reported to be responsible for various ailments (Acton et al, 2009;Bhalla et al, 2007;Foster et al, 2014;Gries et al, 2005;Hansen et al, 2006). In this context, probiotic LAB strains having a propensity to adhere onto the ECM such as collagen and mucin could bear interesting therapeutic potential to prevent invasion of the ECM by S. aureus.…”
Section: Resultsmentioning
confidence: 99%
“…131 Bhalla and colleagues studied patients with skin colonization by S. aureus (including MRSA) and found that the organism was frequently transferred to the hands of HCWs who touched both the skin of patients and surrounding environmental surfaces. 96 Hayden and colleagues found that HCWs seldom enter patient rooms without touching the environment, and that 52% of HCWs whose hands were free of VRE upon entering rooms contaminated their hands or gloves with VRE after touching the environment without touching the patient. 114 Laboratory-based studies have shown that touching contaminated surfaces can transfer S. aureus or Gram-negative bacilli to the fingers.…”
Section: Organism Transfer To Health-care Workers' Handsmentioning
confidence: 99%
“…Because nearly 10 6 skin squames containing viable microorganisms are shed daily from normal skin, 107 it is not surprising that patient gowns, bed linen, bedside furniture and other objects in the immediate environment of the patient become contaminated with patient flora. [93][94][95][96][108][109][110][111][112][113][114] Such contamination is most likely to be due to staphylococci, enterococci or Clostridium difficile which are more resistant to desiccation. Contamination of the inanimate environment has also been detected on ward handwash station surfaces and many of the organisms isolated were staphylococci.…”
Section: Organisms Present On Patient Skin or In The Inanimate Enviromentioning
confidence: 99%
See 1 more Smart Citation